OP0143 CANCER IN GIANT-CELL ARTERITIS PATIENTS: A LARGE NATIONWIDE STUDY. (2nd June 2020) - Ben-Shabat, N.; Dar, L.; Tiosano, S.; Watad, A.; Comanesther, D.; Cohen, A.; Amital, H.
Abstract : Background: The association between giant-cell arteritis (GCA) and malignancy is controversial. Objectives: To asses malignancy rates and risk in GCA patients in a large-scale population-based study. Methods: We utilized the medical database of Clalit-Health-Services for this retrospective cohort study. Follow-up was from January 1, 2002 and continued until death or end of follow-up on September 1, 2018. Incident GCA patients were compared with age-and-sex-matched controls. Hazard-ratios for subtypes of malignancies were obtained by the Cox proportional-hazard model, adjusted for socio-demographic variables and cancer risk factors. Results: The study population included 7, 213 GCA patients and 32, 987 age- and sex-matched controls who were not diagnosed with the disease. The mean age of GCA diagnosis was 72.3±9.9 years (median 73.1 years) and 69.1% were women. At Kaplan–Meier survival analysis, assessing cumulative cancer-free survival in GCA patients and controls, GCA patients had worse curve than controls (chi-squared = 49.84; degrees of freedom = 1; p < 0.0001; Figure 1 ). At the cox-survival analysis adjusted for age, sex, SES and cancer risk factors GCA patients showed increased risk for overall cancer (HR 1.29 [95%CI 1.20-1.39]), kidney cancer (HR 1.60 [95%CI 1.15-2.23]), sarcoma (HR 2.14 [95%CI 1.41-3.24]), acute-leukemia (HR 1.81 [95%CI 1.06-3.07]), chronic-leukemia (HR 1.82 [95%CI 1.19-2.77]), Hodgkin's lymphoma (HR 2.42 [95%CI 1.12-5.20]), non-Hodgkin's lymphoma (HR 1.66 [95%CI 1.21-2.29]) and multiple myeloma (HR 2.40 [95%CI 1.63-3.53) (Table 1 ). The time (mean [months] ± SD) to the diagnosis of any malignancy was significantly shorter in GCA patients (48.6 ± 41.3) compared to controls (58.1 ± 43.6; p<0.001). Conclusion: GCA patients are at increased risk for sarcoma, kidney cancer, hematological malignancies and overall malignancies compared to age-and-sex matched controls from the general population. References: [1]Watad A, McGonagle D, Bragazzi NL, Tiosano S, Comaneshter D, Shoenfeld Y, et al. Autoantibody status in systemic sclerosis patients defines both cancer risk and survival with ANA negativity in cases with concomitant cancer having a worse survival. Oncoimmunology 2019;8:e1588084. [2]Ben-Shabat N, Tiosano S, Shovman O, Comaneshter D, Shoenfeld Y, Cohen AD, et al. Mortality among patients with giant-cell arteritis: A large-scale population-based cohort study. J Rheumatol 2019; Disclosure of Interests: None declared